Neuritogenic and in vitro antioxidant activities of Malaysian Gracilaria manilaensis Yamamoto & Trono - Pang, Jun Rui; Goh, Ming Jun; Phang, Siew Moi; Wong, Kah Hui; Yow, Yoon Yen * (SpringerLink, 2018)
Numerous marine-based compounds have been identified as having diverse biological activities. Gracilaria manilaensis Yamamoto & Trono is a red agarophyte endemic to the Malaysia coastal area. It is used as a gelling and thickening agent for food industries. In this study, the rat pheochromocytoma cell line (PC-12Adh) was employed as in vitro model to investigate the neuritogenic activities in hot aqueous, methanol, and ethanol extracts of G. manilaensis. Phytochemical contents and in vitro antioxidant activities of the extracts were also determined. All G. manilaensis extracts were found to increase the percentage of neurite-bearing cells and upregulated the neuronal cytoskeleton of PC-12Adh cells with no inhibition across the tested concentration range (0–0.15 mg mL−1). The methanol and ethanol extracts had higher phenolic and flavonoid contents than the hot aqueous extract. They also showed higher antioxidant activities against 2,2-diphenyl-1-pircryhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) free radicals and higher reducing power compared to the hot aqueous extract. It is believed that G. manilaensis may possess potent bioactive compounds that mimic the neuroactivity of the nerve growth factor (NGF) for neuronal survival, development, and differentiation. It has been suggested that agar producer G. manilaensis might be a promising dietary supplement for cognitive health in the prevention of neurological disorders.